On the formation of oxide inclusions in the high nitrogen chromium-manganese steel produced by the Wire and Arc Additive Manufacturing - Xiaoyong Zhang; Qiushi Zhao; Chenyu Liu; Yong Peng; Yong Huang; Jian Kong; Kehong Wang (Journal of Materials Research and Technology)
Oxide inclusions significantly impeded the mechanical properties of the Wire and Arc Additive Manufacturing (WAAM) made high nitrogen Cr–Mn austenite stainless steels (HNSs). This paper focused on the inclusions' component, crystallization characteristics and formation mechanism. Results revealed that there are two types of inclusions: the round-shape nano-size inclusion (Type-I) and the micron-size island-shape inclusion (Type-II). The Type-I inclusion usually consists of the MnO particle or the combination of the MnO, Si-oxides and precipitations (MnS or Cr2N). Most of the Type-I oxide inclusion is located in the range between 300 nm and 700 nm,the number of Type-I oxide inclusion takes the main part of 69.7%.With higher content, smaller size and more even distributions, the isolated Type-I oxide inclusions would be beneficial to the mechanical properties owing to the Orowan strengthening mechanism. The Type-II inclusion is mostly composed of the MnO matrix and the coherent chromite spinel (MnCr2O4). In general, the larger the size, the more serious the negative impact on mechanical properties. And there was a strong negative correlation between the size and quantity of type II oxide inclusions. After heat treatment, abundant phase transformations occurred in the Type-II inclusions and some harmful phases (Sigma, MnS et cl.) were often found in or around the inclusions with specific orientation relationships. During deposition, the unstable droplet transformation and the trapped residual slag were the main causes for the inclusions in the molten pool.